Strategic Marketing Management for Online Shopping and Business Adaptation to Changing Consumer Behavior: A Narrative Review Approach - Sitti Mujahida Baharuddin; Abdul Latief; Thamrin Abduh; Irwan Rasyid (Universitas Dharma Wacana, 2022)
In the era of innovation-driven business transformation, three main dimensions attract attention: The Application of AI in Global Marketing, Business Model Innovation in Cultural and Creative Industries post-crisis COVID-19, and Strategic Information Management in Greek SMEs during the Economic Crisis. These abstract details the impacts, challenges, and opportunities embodied in these three aspects, highlighting the importance of equitable distribution of innovation, sustainability in business models, and ethical and privacy protection in information management. The research method in this study utilizes a narrative literature review approach. This study presents significant findings across three key dimensions of business transformation: Application of AI in Global Marketing, Business Model Innovation in Cultural and Creative Industries after the COVID-19 crisis, and Strategic Information Management in SMEs during the Economic Crisis. The findings provide deep insights into the impact of technology, strategic responses to environmental changes, and the strategic role of SMEs in overcoming the economic crisis. The findings of this study highlight that business transformation in the age of innovation requires a balanced and inclusive approach. Technology adoption should be mindful of its impact on economic inequality, innovation needs to be driven by open ecosystem partnerships, and strategic information management is key to SMEs' resilience in the face of economic crisis. To summarize, these challenges demand holistic, collaborative, and sustainable solutions.